Succession characteristics and assembly process of soil microbiome at reclaimed farmlands in coal mining area - Li, Jianhua; Li, Zixu; Sun, Yanwen; Lu, Jinjing; Zhang, Qiang; He, Xinhua; Xu, Minggang (Frontiers in Microbiology, 2025)
Clarifying the succession patterns and assembly mechanisms of soil bacterial and fungal communities across reclamation chronosequences is essential for restoring soil health and ensuring ecological stability in mining areas. We analyzed soil microbial diversity, composition, co-occurrence network structure, and assembly processes using 16S rDNA/ITS sequencing and null models at 0 (R0), 1 (R1), 6 (R6), and 10 (R10) years of post-reclamation. Results showed that (1) Compared to R0, the R10 treatment resulted in significant increases in soil organic matter (SOM), total nitrogen (TN), available phosphorus (AP), and available potassium (AK) by 2.1-fold, 1.3-fold, 1.5-fold, and 0.4-fold, and also in activities of β-glucosidase (BG), N-acetyl-β-glucosaminidase (NAG), and leucine aminopeptidase (LAP), by 17-fold, 8.7-fold, and 1.8-fold, respectively (p < 0.05). (2) Rising bacterial diversity (Shannon, Chao1) over time, contrasting with fungal diversity that declined initially before recovering. (3) As the reclamation progressed, the network complexity was increased for both bacteria and fungi, improving stability. The number of bacterial keystone taxa was first increased and then decreased, with Bacillota (formerly Firmicutes) being the dominant keystone phylum. Bacteroidetes, Proteobacteria, and Acidobacteria exhibited rapid temporal responses. The fungal keystone taxa increased progressively, with Ascomycota as the dominant keystone phylum, while Basidiomycota and Mortierellomycota responded rapidly. (4) Enhanced bacterial functional potential (chemoheterotrophy, aerobic chemoheterotrophy, nitrification) and fungal saprotrophic capacity (undefined, wood saprotrophs) (5) Community assembly involved both deterministic (bacteria: dominated by heterogeneous selection) and stochastic processes (fungi: dispersal limitation/undominated). The partial least squares path modeling (PLS-PM) analysis showed that both the reclaimed coal mining and undisturbed normal farmland (NL) soils directly influenced microbial diversity and indirectly shaped microbial communities by influencing their assembly processes. These results underscore the critical role of reclamation in rebuilding soil microbial communities and restoring ecological functions in coal-mining areas.